Generalization of metric spaces and some fixed point theorems - Elmabrok, Abdelhamid; Alkaleeli, Sameehah (Libyan Journal of Science &Technology, 2022)
The primary purpose of this paper is to adduce the concept of extended metric spaces, inspired by the concepts of metric space and an extended metric space. We also create some fixed-point theorems arising in this space.